Influence of uniaxial tension and compression on shear strength of concrete slabs without shear reinforcement under concentrated loads. (15th August 2017) - Bui, T.T.; Nana, W.S.A.; Abouri, S.; Limam, A.; Tedoldi, B.; Roure, T.
Highlights: A database of experimental tests of RC slabs under concentrated load was addressed. Influence of the axial compression/tension load on the shear strength was studied. Axial tension forces equal to 0.28 f ctm reduced the shear capacity up to 30%. Experimental tests were compared to Eurocode 2, ACI 318-14 and AFCEN ETC-C. Abstract: Under the shear load, reinforced concrete structures may be simultaneously subjected to the axial tensile or compressive forces due to shrinkage in restrained members, earthquake, tornado, and so on. Until now, no experiment addressing the effect of the uniaxial load on the shear resistance of reinforced concrete slab has been reported in the literature. All the experimental tests found in the literature were conducted on panel and beam (or wide beam) specimens. The current shear design provisions with axial load (ACI 318 and Eurocode 2) were developed based solely on panel and beam tests and not slab tests. Therefore, the current shear design codes applied to slab structures under the effect of axial forces urgently need revision. The present research studies the shear strength tests of slabs under the concentrated load simply supported on four sides. The effect of the tension/compression forces on the shear capacity was studied on full-scale slabs without shear reinforcement, a design similar to the slabs used in nuclear buildings, under a concentrated load near support. Experimental tests were conducted to quantify the shear capacity and the associated failure modes with the influence of axial forces. In this study, a series of seven tests on seven full-scale slabs measuring 4 m × 2.6 m × 0.3 m is presented. The experiments were used to evaluate the pertinence of Eurocode 2 in terms of shear in reinforced concrete slabs with axial load, to compare these results to the AFCEN ETC-C code used for nuclear buildings, and to compare them to the ACI 318 code. The results showed that the axial tension forces equal to 0.28 f ctm (average concrete tensile capacity) reduced the shear capacity up to 30% in the concrete slab experiments conducted.